Analysis of Food Additives and Their Effects on Flavor Perception in Brazil - Augusto , Maria (International Journal of Food Sciences, 2023)
Purpose: The aim of the study was to investigate analysis of food additives and their effects on flavor perception Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Food additives have diverse effects on flavor perception. Some, like MSG, enhance umami, while artificial sweeteners offer sweetness without calories but may have aftertastes. Salt amplifies saltiness but can lead to overconsumption. Emulsifiers and stabilizers influence texture and mouthfeel. Effects vary among individuals due to genetics and preferences, emphasizing the need for personalized food product development and labeling. Understanding these complexities is crucial for the food industry to create appealing and healthy products. Unique Contribution to Theory, Practice and Policy: Sensory Evaluation Theory, Expectation Theory and Psychophysics Theory may be used to anchor future studies on analysis of food additives and their effects on flavor perception. Food manufacturers should prioritize consumer-centric approaches when incorporating additives into their products. Policymakers should consider establishing clearer regulations and guidelines regarding the usage and labeling of food additives.